2009
DOI: 10.2489/jswc.64.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-nitrogen patterns in the Raccoon River Basin related to agricultural practices

Abstract: Nitrate-N concentrations in the Raccoon River have increased beginning in the early 1970s. Since this river is the predominant water supply for the City of Des Moines in Iowa, there is concern about the potential long-term impacts of these trends. Improvements in water quality from agricultural watersheds are critical to protect the water supply, and understanding the factors affecting water quality will lead to potential changes in agricultural management to improve water quality. The historical database of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 21 publications
4
123
0
Order By: Relevance
“…Nitrate-N concentrations greater than 6.0 mg L −1 are common in surface waters in Iowa, although many watersheds have significantly more row crop production than present in the Rathbun Lake watershed (Jaynes et al 1999;Tomer et al 2008;Hatfield et al 2009 , the streams in the watershed carry significant amounts of sediment, likely a result of stream bank erosion (Zaimes et al 2008;Tufekcioglu et al 2012). Seasonal sediment and nutrient loads were not calculated as sufficient stream flow data are not available.…”
Section: Surface Water Characteristics In the Watershedmentioning
confidence: 99%
“…Nitrate-N concentrations greater than 6.0 mg L −1 are common in surface waters in Iowa, although many watersheds have significantly more row crop production than present in the Rathbun Lake watershed (Jaynes et al 1999;Tomer et al 2008;Hatfield et al 2009 , the streams in the watershed carry significant amounts of sediment, likely a result of stream bank erosion (Zaimes et al 2008;Tufekcioglu et al 2012). Seasonal sediment and nutrient loads were not calculated as sufficient stream flow data are not available.…”
Section: Surface Water Characteristics In the Watershedmentioning
confidence: 99%
“…Extensive hydrologic modifications, including channelization and subsurface tile drainage, are common in watersheds dominated by intensive corn-soybean production in the midwestern United States (Baker et al, 2008). This is a "leaky" system, particularly for nitrate N, and large nutrient loads are carried downstream even when farmers follow best management practice recommendations (Royer et al, 2006;Baker et al, 2008;Hatfield et al, 2009;David et al, 2010). Policies and plans to address the loss of nutrients from agricultural watersheds have been relatively ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…However, the corn-soybean rotation became dominant in Midwestern agriculture during the same time and is also associated with water quality changes. Hatfield et al (2009) found that increased nitrate-N concentrations in the Raccoon River since 1970 were related to shifts in crop production that replaced small grains and hay with corn and soybean crops. Combined, these changes result in increased discharge rates and nitrate-N concentrations that are correlated with one another, particularly where agricultural subsurface drainage is extensive (Schilling and Lutz 2007;Tomer et al 2008).…”
Section: Implications For Aquatic Systemsmentioning
confidence: 99%